(untitled) (Fiep Bulletin - online, 2016)
Complementary feeding (CF) should be started from 6 months of the infant’s life, which is, along with breastfeeding, reducing child mortality. This study aimed to describe the knowledge about the introduction of healthy CF of pregnant women and mothers of infants <3 months enrolled in the Municipal Program to Fight Malnutrition - Pregnant women, at the Coordination of the Technical Area of ??Food and Nutrition - Catan/Macaé-RJ. A descriptive study of primary basis, conducted in April/2013, with pregnant women and mothers of infants <3 months enrolled in the Municipal Program to Fight Malnutrition - Pregnant women who agreed to participate and signed an informed consent. Health PET scholarship holders, on the day of delivery of the benefit, conducted interviews using a structured form. We interviewed 21 pregnant women, representing 53% of the clientele. About 50% were 20-30 years old; 57.1% had <1 minimum wage (MW); 47.6% had incomplete primary education. Regarding knowledge about the beginning of the introduction of CF, 81% answered correctly that it must be from the sixth month of life, and 61.9% reported that they should be offered two baby foods of fruit and 1 salty, while maintaining breastfeeding. The family income was moderately and negatively associated with early CF (rs = -0.56, p <0.01). Younger mothers believe that infant feeding needs fixed and rigid schedules between the meals (rs = 0.43, p <0.05), contrary to the recommendation. We conclude that some responses indicated unknowns about the foods and preparations that must be offered on complementary feeding.